Assessment of Matrix Cracking and Fiber Breakage in Hybrid Composite Materials. - Aditya Sahu (International Journal of Fracture Mechanics and Damage Science, 2025)
Hybrid composite materials, combining two or more distinct fiber or matrix constituents, have emerged as advanced structural solutions for aerospace, automotive, marine, and civil engineering applications. However, their complex microstructure makes them susceptible to multiple interacting damage mechanisms, particularly matrix cracking and fiber breakage. This study provides a comprehensive assessment of these damage modes, emphasizing their initiation, evolution, and combined effects on the mechanical integrity of hybrid composites. Matrix cracking typically originates from micro-level stress concentrations, thermal residual stresses, and cyclic loading, progressively forming interconnected crack networks that degrade stiffness and promote moisture ingress. Fiber breakage, on the other hand, is primarily influenced by fiber type, interfacial bonding strength, and the heterogeneity of load transfer in hybrid architectures. The interaction between these mechanisms accelerates damage propagation: matrix cracks serve as pathways for stress localization, leading to premature fiber breakage, while broken fibers further intensify local stress fields, fostering additional matrix cracking. Analytical, numerical, and experimental approaches—including micro-mechanical modeling, acoustic emission monitoring, computed tomography, and digital image correlation—are critically reviewed to evaluate their capability in capturing damage progression. The findings highlight that hybridization strategies, such as fiber stacking sequences, fiber mixing ratios, and tailored interphases, significantly influence damage tolerance and failure patterns. This assessment underscores the need for integrated characterization and modeling frameworks to accurately predict service life and optimize the design of hybrid composites. The study contributes to advancing reliable, durable, and high-performance hybrid composite structures through improved understanding of matrix cracking and fiber breakage mechanisms.
Keywords: Damage mechanisms; Fiber breakage; Hybrid Composite Materials; Interfacial bonding; Matrix cracking; Mechanical behavior; microstructural analysis